MEMANFAATKAN TEKNOLOGI INOVASI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN PRESTASI DI SEKOLAH SMK PEMBANGUNAN - Ahmad Khusnaeni (ADISAM PUBLISHER, 2026)
The use of technology in learning at Development Vocational Schools has a big impact on student achievement through various learning media innovations. From the use of online platforms to interactive simulations, technology has opened the door to learning that is more engaging, eflective and adaptive to student needs. The impact is not only limited to understanding the material and practical skills, but also on students' learning motivation. However, to achieve optimal eflectiveness, continuous eflorts are needed in developing teacher expertise, increasing access to technology, and integrating technology into the curriculum as a whole. With these steps, it is hoped that Development Vocational School can create a dynamic and inclusive learning environment, and better prepare students to face the challenges of the increasingly complex world of work in this digital era.